Books or Knives: The Proof is in the Pudding - Rickey Dandridge (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2016)
This research aims to analyze the effects of post-secondary business education, post-secondary culinary training, and/or personal characteristics on the success level of restaurateurs. This study attempts to give insight as to whether formalized business education and/or culinary training translates into higher performance when compared to enterprises where management develops on-the-job learned behavior. To achieve this objective, a qualitative case study was conducted on five local restaurateurs in one Southeastern market. Results show successful restaurateurs effectively management human resources, have prior industry experience, and outsource and/ or automate processes to achieve work-life balance.